(untitled) (Fiep Bulletin - online, 2013)
Despite the technical advancements found in the techniques of dialysis in recent years, patients with end-stage renal disease (ESRD) on hemodialysis show intolerance to exercise, due mainly to the decline in muscle strength as a result of dysfunction and atrophy of skeletal muscle and changes Metabolic. Objective: This study aimed to demonstrate the profile and assess exercise capacity of patients with ESRD on hemodialysis, in both sexes. Methods: Patients were evaluated using the tests of distance in six minutes (6MWT) and Shuttle Walk Test (SWT), spirometry, manometry, maximum oxygen consumption (VO max) calculated by SWT and the quadriceps muscle strength by testing a repetition maximum (1RM). We studied 58 patients 2 (32 male, 48.2 ± 13.2 of mean age) on hemodialysis. The data were expressed as mean, standard deviations, medians, proportions and minimum and maximum values. We used the Student t test to compare mean differences between the sexes. The statistical significance was set for á = 5% (p <0.05). Results: The patients with ESRD had reduced exercise capacity, reduced muscle strength of the quadriceps, reduced lung function and respiratory muscle strength and low maximum oxygen consumption. Conclusion: The results suggests that the patients showed significant functional changes and can certainly be evaluated by the tests proposed, with low cost and high practicality. These tests can also be used in the evaluation and development of physical activities supervised.